Facile synthesis of 2D Al-TCPP MOF nanosheets for efficient sonodynamic cancer therapy. (14th March 2023) - Zhou, Zhan; Wang, Tao; Hu, Tingting; Cheng, Chunhua; Yu, Shilong; Li, Hai; Liu, Shuyan; Ma, Lufang; Zhao, Meiting; Liang, Ruizheng; Tan, Chaoliang
Abstract : 2D Al-TCPP MOF nanosheets were prepared via a simple solvothermal synthesis method without the need for any surfactants and were found to be an effective sonosensitizer for sonodynamic cancer therapy. Abstract : Two-dimensional (2D) metal–organic framework (MOF) nanosheets have been widely explored in recent years as diagnostic and therapeutic reagents for cancer therapies, including photodynamic therapy, chemodynamic therapy, radiation therapy, and catalytic therapy, because of their appealing physicochemical properties. Herein, we report the first preparation of 2D Al-TCPP (TCPP: tetrakis(4-carboxyphenyl)porphyrin) MOF nanosheets, for use as an effective sonosensitizer for sonodynamic cancer therapy, via a simple solvothermal synthesis method without the need for any surfactants. The 2D Al-TCPP nanosheets have a size of 160–200 nm and a thickness of 18.4–26.5 nm and were synthesized by changing the ratio of water to N, N -dimethylformamide. Interestingly, other organic solvents, such as dimethylacetamide, dimethyl sulfoxide, and N -methyl-2-pyrrolidone, can be also used as the co-solvent for the facile synthesis of the 2D Al-TCPP nanosheets. Promisingly, the Al-TCPP nanosheets generate a much higher yield of reactive oxygen species ( i.e., singlet oxygen ( 1 O2 ) and hydroxyl radical (˙OH)) under ultrasound treatment than free TCPP molecules, suggesting that embedding the TCPP molecules in the 2D Al-TCPP nanosheets could significantly enhance the sonodynamic cancer therapeutic activity. Both the in vitro and in vivo results prove that, after modification with polyethylene glycol, the Al-TCPP nanosheets can be used as a sonosensitizer for efficient sonodynamic therapy to kill cancer cells and eliminate malignant tumors.